2021
DOI: 10.1016/j.ajhg.2020.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations of genes essential for Müllerian duct and Wölffian duct development in Mayer-Rokitansky-Küster-Hauser syndrome

Abstract: Mayer-Rokitansky-Ku ¨ster-Hauser syndrome (MRKHS) is associated with congenital absence of the uterus, cervix, and the upper part of the vagina; it is a sex-limited trait. Disrupted development of the Mu ¨llerian ducts (MD)/Wo ¨lffian ducts (WD) through multifactorial mechanisms has been proposed to underlie MRKHS. In this study, exome sequencing (ES) was performed on a Chinese discovery cohort (442 affected subjects and 941 female control subjects) and a replication MRKHS cohort (150 affected subjects of mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 29 publications
1
54
0
Order By: Relevance
“…The difference between the null mouse Müllerian phenotypes and our patient phenotypes could be explained by a difference in WNT9B's role in the urogenital system development between humans and mice, domain specific mutations, or the effect of a variable degree of loss of WNT9B function, although the variant in Family 2 is presumably a null variant. As prior reports have suggested WNT9B as a candidate gene for human Müllerian agenesis (Chen et al, 2021;Wang et al, 2014;Waschk et al, 2016), we looked further at the reported variants in these papers (Table 1). The five heterozygous candidate variants for Müllerian agenesis reported by Waschk et al (2016), have allele counts of 1, 348, 55, 0, and 12 in gnomAD v2.1.1 (Karczewski et al, 2020), suggesting that at least three of them are too common to cause this rare anomaly on their own.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference between the null mouse Müllerian phenotypes and our patient phenotypes could be explained by a difference in WNT9B's role in the urogenital system development between humans and mice, domain specific mutations, or the effect of a variable degree of loss of WNT9B function, although the variant in Family 2 is presumably a null variant. As prior reports have suggested WNT9B as a candidate gene for human Müllerian agenesis (Chen et al, 2021;Wang et al, 2014;Waschk et al, 2016), we looked further at the reported variants in these papers (Table 1). The five heterozygous candidate variants for Müllerian agenesis reported by Waschk et al (2016), have allele counts of 1, 348, 55, 0, and 12 in gnomAD v2.1.1 (Karczewski et al, 2020), suggesting that at least three of them are too common to cause this rare anomaly on their own.…”
Section: Discussionmentioning
confidence: 99%
“…One variant was rare but in the 3′ untranslated region and not predicted to impact splicing based on SpliceAI score (Jaganathan et al, 2019), and the other was a missense variant that is now known to have 8 allele counts in gnomAD v2.1.1 (Karczewski et al, 2020), making these unlikely to cause this rare phenotype. Moreover, the heterozygous nonsense variant recently reported by Chen et al is not expressed in WNT9B 's canonical transcript (NM_003396.2) and is in the last exon of the NM_001320458.2 transcript, removing only four amino acids from the WNT9B protein and not predicted to result in nonsense‐mediated mRNA decay (Chen et al, 2021). This variant has two allele counts in gnomAD v2.1.1 (Karczewski et al, 2020) and was not segregated in family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WES data processing was performed using the Peking Union Medical college hospital Pipeline (PUMP) [13,14] developed in-house. Computational prediction tools (Genomic Evolutionary Rate Profiling [GERP] [15], Combined Annotation Dependent Depletion [CADD PHRED-score, GRCh37-v1.6] [16], Sorting Intolerant Form Tolerant [SIFT] [17], Polyphen-2 [18], and MutationTaster [19]) were used to predict the conservation and pathogenicity of candidate variants.…”
Section: Bioinformatic Analysis and Mutation Interpretationmentioning
confidence: 99%
“…Congenital vertebral malformation (CVM) refers to abnormal development of the spine structure presenting as congenital scoliosis, kyphosis, or other congenital vertebral defects and may occur simultaneously with other birth defects or as part of an underlying genetic syndrome [1,2]. In human embryogenesis, the vertebral column develops at 4-6 weeks of gestation from the paraxial mesoderm (PSM) and is closely related to the spinal cord and other organs originating from mesoderm [3][4][5]. Multiple organ defects, most frequently involving the cardiac system, urogenital system, limbs, and spinal cord, have a higher occurrence in CVM than in the general population [3].…”
Section: Introductionmentioning
confidence: 99%